Anti-inflammatory effects of tibial axial loading on knee articular cartilage post traumatic injury. (9th November 2021) - Hazbun, Larry; Martinez, Jose A.; Best, Thomas M.; Kaplan, Lee; Huang, Chun-Yuh
Abstract: Early therapeutic intervention to mitigate inflammatory responses following joint injury may offer a potential strategy to prevent post-traumatic osteoarthritis (PTOA). In-vitro studies have demonstrated uniaxial dynamic compression mitigates the catabolic and apoptotic responses of articular cartilage (AC) in response to mechanical injury. The objectives of this study were (1) to develop a custom device that can apply dynamic tibial axial loading (TAL) to knee AC by mimicking therapeutic, in-vitro loading conditions and (2) to investigate the potential of TAL to reduce the inflammatory response of AC post traumatic acute joint injury using an ex-vivo porcine model. A TAL device was fabricated to apply dynamic compressive loading to knee AC by combining tibial axial compressive loading with continuous passive motion. Computational analyses demonstrated that the loading condition applied to the knee by the TAL device closely simulate uniaxial dynamic compression reported in previous in-vitro studies. Following single impact injury, injured porcine knees were subjected to TAL with a magnitude of 1/4 body weight at a frequency of 1 Hz for 30 min. AC samples were harvested 8 h post injury for analysis of pro-inflammatory cytokine expression (IL-1β and TNF-α). Expression of both cytokines was upregulated following injury; however, the change was notably mitigated in the specimens subjected to TAL. Thus, TAL may be an effective and potentially, practical-to-administer early intervention strategy to mitigate rapidly occurring detrimental events following acute AC injury, potentially slowing down progression to PTOA.